RESEARCH OF THE PHYSICAL AND MECHANICAL PROPERTIES OF FIBERS OF DIFFERENT SELECTION VARIETIES (Multidisciplinary Journal of Science and Technology, 2024)
in this article, the physical mechanical properties of cotton fibers of different selection varieties were analyzed in the testing laboratory of the Department of "textile materials science", as well as by international standards, the quality of cotton fibers was evaluated using a microscope based on Özdst 604-2016 with methods of measurement in the classyor and TEXTECHNO system.